An Appraisal of Cluster Frontline Demonstrations on Mustard Crop in Sawaimadhopur District of Rajasthan - Sharma, Nupur; Roy, Himadri; Maji, Saikat (Indian Journal of Extension Education, 2022)
The study attempted to analyse the overall effectiveness of the Cluster frontline demonstrations (CFLDs) conducted by the Krishi Vigyan Kendra, Sawaimadhopur, from 2018–19 to 2021–22 using Integrated Crop Management technologies on mustard. A combination of experimental and before-after research designs was used, and 492 beneficiaries were selected for conducting the CFLDs. The obtained results from both the demonstrated and local check plots were compared, and the average yield of the improved mustard variety Giriraj from the demonstrated plots was significantly higher than that from the local check plots during these years. On average, extension and technology gaps were recorded as 4.82 q/ha and 5.99 q/ha, respectively. The average technology index was 21.79 per cent, and the lowest was noticed in the last season of the demonstrations, indicating the increased adaptability and efficiency of recommended technologies in field conditions. The average net returns and benefit-cost ratio from the demonstrated plots outperformed the local check plots in all four seasons. Overall, the CFLDs positively impacted the mustard growers of that particular area and motivated them to adopt the recommended practises for higher yield and profitability.
Keywords: Mustard; ICM; CFLDs; Technology gap; Extension gap; Impact; Horizontal spread